Using formalin fixed paraffin embedded tissue to characterize the microbiota in p16-positive and p16-negative tongue squamous cell carcinoma: a pilot study - Zhan Yuanbo; Liu Tianyi; Song Xuejing; Liu Xinpeng; Wang Jianqun; Xu Wenxia; Geng Jingshu (BMC, 2024)
Abstract Background Tongue squamous cell carcinoma (TSCC) is the most common oral cavity cancer, and p16 immunohistochemistry is an exact and available tool in the prognostic and predictive characterization of squamous cell cancers in the head and neck. Microorganisms have a close relationship with the development of TSCC. However, the association between oral bacteria and p16 status has not been well defined in the case of TSCC. Compared with traditional clinical microbial collection methods, formalin-fixed paraffin-embedded (FFPE) tissue samples have several advantages. Methods To compare the microbiota compositions between p16-positive and p16-negative patients with TSCC, we performed a small pilot study of microbiological studies of TSCC by paraffin tissue. DNA from FFPE tissue blocks were extracted and microbiomes were profiled by sequencing the 16 S-rRNA-encoding gene (V1-V2/V3-V4/V4 regions). Alterations in the functional potential of the microbiome were predicted using PICRUSt, Tax4Fun, and BugBase. Results A total of 60 patients with TSCC were enrolled in the study, however, some challenges associated with DNA damage in FFPE tissues existed, and only 27 (15 p16-positive and 12 p16-negative) passed DNA quality control. Nevertheless, we have tentatively found some meaningful results. The p16 status is associated with microbiota diversity, which is significantly increased in p16-positive patients compared with p16-negative patients. Desulfobacteria, Limnochordia, Phycisphaerae, Anaerolineae, Saccharimonadia and Kapabacteria had higher abundances among participants with p16-positive. Moreover, functional prediction revealed that the increase of these bacteria may enhance viral carcinogenesis in p16-positive TSCC. Conclusions Bacterial profiles showed a significant difference between p16-positive TSCC and p16-negative TSCC. These findings may provide insights into the relationship between p16 status and the microbial taxa in TSCC, and these bacteria may provide new clues for developing therapeutic targets for TSCC.